Electronic Student Worksheet Based on APOS Theory to Improve the Strategic Competence of Fourth Grade Elementary School Students - Ni Komang Jinggan Sri Ganitri; Gusti Ngurah Sastra Agustika; Dewi Anzelina (Universitas Pendidikan Ganesha, 2025)
Students struggle to understand fractions due to limited abstract thinking skills and inadequate teaching methods. This study develops and tests the feasibility and effectiveness of an Electronic Student Worksheet based on APOS Theory to enhance fourth-grade students' strategic competence. The research uses the ADDIE-based R&D method, involving analysis, design, development, implementation, and evaluation. Subjects include content, design, and media experts, as well as students (three individual trials, nine small group trials, and twelve effectiveness tests). Data collection involves observation, interviews, questionnaires, and tests, analyzed using descriptive and inferential statistics. Feasibility tests show high ratings: content experts (95.8%), design experts (82.5%), media experts (92.3%), individual trials (93.3%), and small group trials (91.6%), classified as